Wait, skates! - Johnson, Mildred D. (Mildred Dawes); Dunnington, Tom (Chicago : Childrens Press, 1983)
A child putting on roller skates for the first time finally teaches them to wait.
1.
1.5
K-3
P-2.
Keywords: Roller skating -- Fiction; Roller skating -- Fiction